Morndumath Application Against HOTS in Building Materials for Middle School Students - Utin Desy Susiaty; Nurul Fitria; Marhadi Saputro (Absis: Mathematics Education Journal, 2022)
This study aims to produce Morndumath application learning media on Higher Order Thinking Skills (HOTS) in building materials for class VIII SMP Negeri 1 Sungai Kakap students who reach the level of validity, practicality, and effectiveness. This study uses the ADDIE development design model, which consists of five main stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were eighth grade students of SMP Negeri 1 Sungai Kakap. The instruments used in this study were validation sheets, questionnaires, and pretest posttest questions. Based on the results of the first study, the validation of the Morndumath application against HOTS was with the average value of the three experts of 85.25% in the very valid criteria with the very good category. The second is the value of practicality, seen from the value of the questionnaire filled out by the teacher and all students who were accumulated so that a percentage of 87.61% was obtained with very practical criteria. Furthermore, the effectiveness, seen from the results of statistical tests using the pretest and posttest scores of students with t-test results, namely – t-count < - t-table significant = 5% (???? = 0.05). This means that there is an increase in the value of student learning outcomes in high-level abilities, so the Morndumath application is categorized as effective.